2019
DOI: 10.1177/0022034519828701
|View full text |Cite
|
Sign up to set email alerts
|

Use of CBCT Guidance for Tooth Autotransplantation in Children

Abstract: Tooth autotransplantation (TAT) offers a viable biological approach to tooth replacement in children and adolescents. The aim of this study was to evaluate the outcome of the cone-beam computed tomographic (CBCT)-guided TAT compared to the conventional TAT protocol and to assess the 3-dimensional (3D) patterns of healing after CBCT-guided TAT (secondary aim). This study included 100 autotransplanted teeth in 88 patients. Each experimental group consisted of 50 transplants in 44 patients (31 males and 19 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 33 publications
(38 reference statements)
0
62
1
3
Order By: Relevance
“…In our retrospective study, the tooth autotransplantation, using 3D replica, was an efficient method with a 100% success rate during two-years follow-up, according the success criteria previously mentioned. As EzEldeen reported that the CBCT-guided tooth autotransplantation could be adopted as an alternative for the conventional approach with the help of 3D analysis [20]. Verweij et al [17] also…”
Section: Discussionmentioning
confidence: 99%
“…In our retrospective study, the tooth autotransplantation, using 3D replica, was an efficient method with a 100% success rate during two-years follow-up, according the success criteria previously mentioned. As EzEldeen reported that the CBCT-guided tooth autotransplantation could be adopted as an alternative for the conventional approach with the help of 3D analysis [20]. Verweij et al [17] also…”
Section: Discussionmentioning
confidence: 99%
“…In our retrospective study, the tooth autotransplantation, using 3D replica with or without GBR, was an efficient method with a 100% success rate during two-years follow-up, according the success criteria previously mentioned. As EzEldeen reported that the CBCT-guided tooth autotransplantation could be adopted as an alternative for the conventional approach with the help of 3D analysis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Lee and Shahbazian have used computer-aided rapid prototyping for tooth transplantation and shorten the extraoral time [18,19]. EzEldeen et al reported that the CBCT-guided tooth autotransplantation could improve the survival rate to 92% compared with conventional way, and 3D analysis can provide insights into the patterns of healing [20].…”
Section: Introductionmentioning
confidence: 99%
“…The use of intraoral scanners and computer-aided systems (computer-aided design/computer-aided manufacturing CAD/CAM) enabled digitized prosthodontics [2,3]. Moreover, 3D-printing is increasingly gaining ground, allowing patient-customized guided surgery [4,5]. Furthermore, recent innovations like virtual and augmented reality created new visualization systems for anatomic exploration [6].…”
Section: Introductionmentioning
confidence: 99%